Metagenomic analysis reveals the microbiome and antibiotic resistance genes in indigenous Chinese yellow-feathered chickens - Xu, Yibin; Huang, Yulin; Guo, Lijin; Zhang, Siyu; Wu, Ruiquan; Fang, Xiang; Xu, Haiping; Nie, Qinghua (Frontiers in Microbiology, 2022)
Yellow-feathered chickens have great nutritional value and are widely and traditionally used in China, on an industrial scale, as broilers. The presence of intestinal microbes has been shown to correlate with poultry performance, and they serve as an essential reservoir of antibiotic resistance genes (ARGs). Notably, antimicrobial resistance is a major public health concern. Here, we investigated functional characteristics of the gut microbiome of indigenous Chinese yellow-feathered chickens (the Huiyang Bearded, Xinghua, Huaixiang, Zhongshan Shanlan, Qingyuan Patridge, and Yangshan chickens) through metagenomic sequencing and reconstructed 512 draft genomes. Furthermore, we assessed the functions of intestinal microbial communities and examined the ARGs within them. Results showed that the microbial populations of yellow-feathered broilers were primarily dominated by Bacteroidetes and Firmicutes at the phylum level and Bacteroides at the genus level. Furthermore, the Qingyuan Patridge chicken showed a significantly higher abundance of the Prevotella genus than that of the other five breeds of chicken. Principal coordination analysis indicated significant differences in the structures of microbial communities and the ARGs, based on the binary Jaccard distance (analysis of similarities ANOSIM R = 0.747, P = 0.001 and R = 0.525, P = 0.001, respectively), among the six breeds of chicken. Moreover, 989 ARGs conferring tetracycline, multidrug, or aminoglycoside resistance were identified, which represented more than 80% of the faecal resistomes. Furthermore, tet(Q) was the most abundant gene in yellow-feathered chickens. In addition, we found a greater abundance of resistance genes in the Xinghua chicken, which indicated that Xinghua chickens are highly resistant to antibiotics. Overall, our findings revealed differences in the gut microbial community structure of indigenous Chinese yellow-feathered broiler breeds and their potential to be used as ARGs and for antibiotic resistance, and reconstruct the yellow-feathered chicken gut microbial community genomes. The current data significantly improves our knowledge of the gut microbiome and antibiotic resistance, particularly in the indigenous yellow-feathered Chinese chicken.